PENGARUH E-TRUST DAN ONLINE CUSTOMER REVIEW PADA MINAT PEMAKAIAN PLATFORM PEMBAYARAN FLIP DI BANDAR LAMPUNG - Dzakiansyah Ridho Sanggeriho; Driya Wiryawan; Dwi Asri Siti A (Nusantara Hasana Journal, 2026)
The development of digital technology has driven the increasing use of financial technology (fintech) services in various public financial transaction activities. One of the developing fintech platforms in Indonesia is Flip, which offers interbank transfer services without administrative fees. The problem in this study is whether E-Trust affects the interest in using the Flip payment platform in Bandar Lampung and whether Online Customer Reviews affect the interest in using the Flip payment platform in Bandar Lampung. The purpose of this study is to determine the role of E-Trust on the interest in using the Flip payment platform in Bandar Lampung and to determine the role of Online Customer Reviews on the interest in using the Flip payment platform in Bandar Lampung. This study utilized a quantitative method with a purposive sampling technique. Data were obtained through the distribution of questionnaires to 100 Flip application users in Bandar Lampung. The data analysis technique used was multiple linear regression analysis with the assistance of the SPSS program. The results showed that E-Trust had a positive and significant effect on the interest in using the Flip payment platform in Bandar Lampung. Online Customer Reviews simultaneously had a positive and significant effect on the interest in using the Flip payment platform in Bandar Lampung. This proves to be effective in increasing public interest in using the Flip payment platform.